Aquivion®–carbon composites via hydrothermal carbonization: amphiphilic catalysts for solvent-free biphasic acetalization. Issue 12 (3rd March 2016) - Fang, Wenhao; Fan, Zhaoyu; Shi, Hui; Wang, Sheng; Shen, Wei; Xu, Hualong; Clacens, Jean-Marc; De Campo, Floryan; Liebens, Armin; Pera-Titus, Marc
Abstract : Amphiphilic Aquivion®–carbon composites prepared by hydrothermal carbonization of polysaccharides (guar gum or cellulose) were able to catalyze the biphasic acetalization reaction between dodecyl aldehyde and ethylene glycol in the presence of Pickering emulsions. Abstract : One-pot hydrothermal carbonization of polysaccharides ( i.e. guar gum or cellulose) with Aquivion® perfluorosulfonic superacid at 180 °C produced new amphiphilic Aquivion®–carbon composites. The materials stabilized dodecyl aldehyde/ethyleneglycol Pickering emulsions, and thus efficiently catalyzed the solvent-free biphasic acetalization reaction under moderate conditions with excellent reusability.